Skills of the future for a high‐performing workforce: Implications of recent evidence for the public sector. (14th December 2021) - Delisle, Marc; Lajoie, Denis
Abstract: Advances in technology spur speculation as to the challenges inherent to the future of work and the skills and abilities that will be necessary to meet these challenges. We challenge this speculation by reviewing scientific evidence regarding 20 so‐called skills and abilities of the future that are identified in five influential reports in the popular literature (i.e., research‐oriented but non‐academic publications intended for government or business audiences), while focusing on empirical evidence of relationships with performance on the job. We find that many of the skills identified in the popular literature surveyed have not been empirically tested, that when they were tested the quality of data is often very limited, and that there is much conceptual confusion regarding skills and abilities in the popular literature. Now, and for the foreseeable future, general mental ability appears to be the best validated factor upon which performance can be built. Sommaire: Les progrès technologiques suscitent la spéculation concernant les défis inhérents à l'avenir du travail et sur les compétences et habiletés qui seront nécessaires pour relever ces défis. Nous remettons en cause cette spéculation en examinant les preuves scientifiques concernant 20 prétendues compétences et aptitudes du futur qui sont identifiées dans cinq rapports influents de la littérature populaire (c.‐à‐d. des publications axées sur la recherche, quoique non académiques, et s'adressant à un public gouvernemental ou de gens d'affaires), tout en nous focalisant sur les preuves empiriques des relations avec le rendement au travail. Nous constatons que bon nombre des compétences identifiées dans la littérature populaire examinée n'ont pas été testées empiriquement, que lorsqu'elles ont été testées, la qualité des données est souvent très limitée et qu'il existe une grande confusion conceptuelle à l'égard des compétences et des aptitudes dans cette littérature. Actuellement, et dans un avenir prévisible, l'intelligence générale semble être le facteur le mieux validé sur lequel bâtir le rendement.